Impact of prepregnancy body mass index on adverse pregnancy outcomes: analysis from the Longitudinal Indian Family hEalth cohort studyAJOG MFM at a Glance - Monica Gudipally, MD; Fouzia Farooq, PhD, MPH; Kalpana Basany, MD; Catherine L. Haggerty, PhD, MPH; Gong Tang, PhD; Govindrao N. Kusneniwar, MD; Guru Rajesh Jammy, PhD, MPH; Clareann H. Bunker, PhD; P.S. Reddy, MD (AJOG Global Reports, 2023)
BACKGROUND: Both high and low maternal prepregnancy body mass index can lead to suboptimal fetal growth and risk of pregnancy complications. In developed countries, nearly half of all women of childbearing age are either overweight or obese, and most data linking maternal body mass index and adverse pregnancy complications are limited to these populations. OBJECTIVE: This study aimed to prospectively evaluate the relationships between prepregnancy body mass index and adverse pregnancy outcomes using the Longitudinal Indian Family hEalth (LIFE) study. STUDY DESIGN: We modeled the relationships between prepregnancy body mass index and adverse pregnancy outcomes such as low birthweight, preterm birth, cesarean delivery, intrauterine growth restriction, miscarriage, and fetal death among 675 women aged 15 to 35 years with singleton pregnancies in the Longitudinal Indian Family hEalth study, a population-based prospective pregnancy cohort study conducted in Telangana, India. Prepregnancy body mass index was calculated as weight in kilograms divided by height in meters squared and was classified into 4 categories using the World Health Organization recommendations for Asian adults. Prepregnancy body mass index was assessed at a mean of 12.3 months before pregnancy. Odds ratios and 95% confidence intervals of adverse pregnancy outcomes were modeled and adjusted for confounders. RESULTS: Obese women had a 3-fold increased risk of cesarean delivery (odds ratio, 3.13; 95% confidence interval, 1.56–6.29) compared with normal-weight women. Those who were overweight also had a marginally increased risk of cesarean delivery, albeit not statistically significant (odds ratio, 1.17; 95% confidence interval, 0.61–2.24). Underweight women had a modestly increased risk of low birthweight, compared with normal-weight women (odds ratio, 1.12; 95% confidence interval, 0.71–1.77), although results were not significant. Conversely, obese (odds ratio, 0.71; 95% confidence interval, 0.28–1.77) and overweight (odds ratio, 0.61; 95% confidence interval, 0.24–1.51) women had a marginally decreased risk of low birthweight. CONCLUSION: Our data suggest that women with elevated prepregnancy body mass index may have a higher risk of adverse pregnancy outcomes, especially cesarean delivery. Although this study has limited generalizability, our findings are generalizable to rural to periurban regions of India. Further studies exploring the translatability of these findings to other populations are needed. In addition, targeted prepregnancy intervention studies and programs that include counseling on optimization of preconception health and lifestyle modification for improvement of subsequent pregnancy outcomes among overweight and obese women are needed.